Negative Emission Power Plants: Thermodynamic Modeling and Evaluation of a Biomass-Based Integrated Gasification Solid Oxide Fuel Cell/Gas Turbine System for Power, Heat, and Biochar Co-Production—Part 1 - Jaiganesh, N.; Kuo, Po-Chih; Woudstra, Theo; Ajith Kumar, R.; Aravind, P. V. (Frontiers in Energy Research, 2022)
Graphical Abstract